2014
DOI: 10.3892/etm.2014.2069
|View full text |Cite
|
Sign up to set email alerts
|

Comparative serum proteome expression of the steroid-induced femoral head osteonecrosis in adults

Abstract: Steroid-induced osteonecrosis of the femoral head (SONFH) is a disabling, aseptic and ischemic disease that develops following steroid therapy. The pathogenesis of SONFH is unclear, so the early diagnosis and treatment for this disease is yet to be established. The purpose of the present study was to identify potential biomarkers for SONFH. The differential expression of serum proteins from patients with SONFH and healthy volunteers was analyzed by the proteomics method. The protein samples were labeled and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Although MRI has made a massive contribution to the early diagnosis of ONFH, the failure to evaluate the activity status and prognosis of the disease results in that numbers of patients miss the opportunities for timely treatment. The proteomics technology has been used to analyze the sera proteins levels which altered in ONFH patients, of which the aim is to explore the biomarkers of ONFH [35]. Previous studies have established the relationship between matrix protein, angiogenic molecule and the occurrence of ONFH in experimental animal models [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Although MRI has made a massive contribution to the early diagnosis of ONFH, the failure to evaluate the activity status and prognosis of the disease results in that numbers of patients miss the opportunities for timely treatment. The proteomics technology has been used to analyze the sera proteins levels which altered in ONFH patients, of which the aim is to explore the biomarkers of ONFH [35]. Previous studies have established the relationship between matrix protein, angiogenic molecule and the occurrence of ONFH in experimental animal models [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…α2‐Macroglobulin is indicated to significantly increase the regenerative capacity of plasma plasmin, while the complex formed by the binding of α2‐macroglobulin and vascular endothelial growth factor inhibits the activity of heparin, resulting in a hypercoagulable state of the blood. Chen et al . confirmed that the level of α2‐macroglobulin in bone tissue of patients with steroid‐induced femoral head necrosis was significantly decreased, which may be related to the hypercoagulability of the blood, hyperlipidemia, free radicals, and degradation of matrix metalloproteinase.…”
Section: Introductionmentioning
confidence: 97%
“…In the last few years, SONFH has attracted extensive attention, various hypotheses have been put forward for the etiological factors involved in corticosteroid-induced osteonecrosis, and it is now considered multiple factors contribute to the development of SONFH, including blood coagulation disorders, abnormal lipid metabolisms [7,8], disorders of the vascular endothelium [9], fat embolism [10], oxidative stress [11][12][13], apoptosis [8], genetic variants, thrombosis, alcohol abuse, long-term corticosteroid use [14], systemic lupus erythematosus, inflammatory bowel disease, and also for immunosuppression after renal transplants [15][16][17]. Though there are many clinical and basis studies about femoral head necrosis in previous studies, it is still unable to clarify the specific pathophysiological mechanism of the process by which corticosteroid administration induces the development of osteonecrosis [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The beginning of proteomic technology applying and screen biomarker in femoral head necrosis is relatively late and there are rare reports [12,13,21,22]. So, in this study, differentially expressed protein in serum among SONFH, TONFH patients and healthy volunteers in Chinese females was compared using iTRAQ, the proteomics study of femoral head necrosis will be helpful to screen potential diagnostic biomarkers for SONFH.…”
Section: Introductionmentioning
confidence: 99%